Peripheral Precocious Puberty of Ovarian Origin in a Series of 18 Girls: Exome Study Finds Variants in Genes Responsible for Hypogonadotropic Hypogonadism - Brauner, Raja; Bignon-Topalovic, Joelle; Bashamboo, Anu; McElreavey, Ken (Frontiers in Pediatrics, 2021)
Background Peripheral precocious puberty of ovarian origin is a very rare condition compared to central form. It may be associated with an isolated ovarian cyst (OC). The causes of OC in otherwise healthy prepubertal girls is currently unknown Methods Exome sequencing was performed on a cohort of 18 girls presenting with prenatal and/or prepubertal OC at pelvic ultrasonography. The presenting symptom was prenatal OC in 5, breast development in 7 (with vaginal bleeding in 3) and isolated vaginal bleeding in 6. All had OC ≥10 mm. The girls had no other anomalies. Four patients had a familial history of ovarian anomalies and/or infertility. Results In 9 girls (50%), candidate or known pathogenic variants were identified in genes associated with syndromic and non-syndromic forms of hypogonadotropic hypogonadism including PNPLA6, SEMA3A, TACR3, PROK2, KDM6A, KMT2D, GNRH1, OFD1, GNRHR, GLI3, INSR, CHD7, CDON, RNF216, PROKR2, GLI3, LEPR. Conclusions In the first study reporting exome sequencing in prepubertal OC, half of the patients with OC carry either previously reported pathogenic variants or potentially pathogenic variants in genes known to be associated with isolated or syndromic forms of congenital hypogonadotropic hypogonadism. Studies of a larger cohort are recommended to establish the causality of these variants.